The Rejection of Techno-Culture in the "Alita Battle Angel" Movie by Robert Rodriguez: An Application of Jean Francois Lyotard’s Postmodernism Theory - Nurdin A; Muarifuddin Muarifuddin; Fina Amalia Masri (ELITE: Journal of English Language and Literature, 2021)
This research aimed to describe The Rejection of Technoculture in the Alita: Battle Angel Movie by using Jean Francois Lyotard Theory. This research used the Descriptive Qualitative Method. The source of the data in this research is Alita: Battle Angel Movie directed by Robert Rodriguez that is published in 2019. The data was collected through watching the movie carefully several times, pausing every scene to read the conversation text, screen shooting the image that related, and taking a note about the data. This research is analyzed by identifying characters that represented the Technoculture, Displaying and interpreting the data about Technoculture by using Postmodernism theory by Jean Francois Lyotard Theory and Drawing the conclusion. The result of this research found that Alita, Zapan, Grewishka are characters that represented the Technoculture (Cyborg and Human Relationship and Hedonism) represented in the Alita: Battle Angel Movie through the power of science and technology, individualism, and rationality. The Rejection of Technoculture depicted through the character of Alita that her power is not evolved from technology but originating from the legendary martial art called Punzer Kuntz before her body is combined with Ido's technological tools. Technology is not necessarily having an important role in the human body as described by the heroine character, Alita herself, whose overall strength did not come from technology. Alita in this movie is a parody because she is a robot that humanized herself. In fact, she shows many aspects of his humanity that humans are busy degrading themselves.